1993
DOI: 10.1017/s0956796800000708
|View full text |Cite
|
Sign up to set email alerts
|

Heap profiling of lazy functional programs

Abstract: We describe the design, implementation and use of a new kind of profiling tool that yields valuable information about the memory use of lazy functional programs. The tool has two parts: a modified functional language implementation which generates profiling information during the execution of programs, and a separate program which converts this information to graphical form. With the aid of profile graphs, one can make alterations to a functional program which dramatically reduce its space consumption. We demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 13 publications
0
39
0
Order By: Relevance
“…At this point (Summer 1995), we became aware of the work by Runciman and Wakeling on profiling of Haskell programs [46]. Based on their system, Hallenberg developed a region profiler for the ML Kit [28].…”
Section: Region Profilingmentioning
confidence: 99%
“…At this point (Summer 1995), we became aware of the work by Runciman and Wakeling on profiling of Haskell programs [46]. Based on their system, Hallenberg developed a region profiler for the ML Kit [28].…”
Section: Region Profilingmentioning
confidence: 99%
“…The analysis of the efficiency of a program can be addressed in two diflPerent ways Runciman and Wakeling, 1992a]. Firstly, this analysis can be done theoretically, that is by reasoning about the way in which the result is computed.…”
Section: Efficient Programsmentioning
confidence: 99%
“…For this reason the testing of the current profiling tools found in this thesis is based purely on the effectiveness of the profiling tools for the development of a very large functional program. This work diflPers from that of Sansom which focuses on the profiling of the Haskell compiler GHC and also the work by Runciman and Wakeling [Runciman and Wakeling, 1993] in which the programmers have experience in the implementation of functional programming languages.…”
Section: The Lolita Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…It is hoped that when time profiling techniques for lazy functional languages [SPJ95] are sufficiently developed, their use will highlight further areas for improvement. Also, although space-profiling is now a well established technology [RW93], its absence from Embedded Gofer has caused certain questions about the memory requirements of applications to be left unanswered. Research into the specific patterns of memory usage found in embedded applications could eventually allow the embedded systems designer a much greater degree of control over the price/performance tradeoff.…”
Section: Future Workmentioning
confidence: 99%